Transferable data exclusivity vouchers are not the solution to the antimicrobial drug development crisis: A commentary on the proposed EU pharma regulation - Berner-Rodoreda, Astrid; Cobelens, Frank; Vandamme, Anne-Mieke; Froeschi, Gunter; Skordis, Jolene; Elil, Renganathan *; t'Hoen, Ellen; Raviglione, Mario; Jahn, Albrecht; Barnighausen, Till (BMJ Publishing Group, 2024)
Access to pharmaceutical products worsened during the COVID-19 pandemic when key developers of active pharmaceutical ingredients and medicinal products prioritised their national markets. These challenges led to a stronger commitment by the European Union (EU) to become more autonomous in developing and providing access to pharmaceutical products for its population.1 In April 2023, the European Commission (EC) proposed a reform of the EU pharma regulation to improve patient-centredness, strengthen the European pharmaceutical industry and incentivise pharmaceutical innovation.1 This reform needs to be approved by the European Parliament. In its present form, it includes the introduction of Transferable Data Exclusivity Vouchers (TDEVs) to address the crisis in antimicrobial innovation. In this commentary, we assess the use of TDEVs as an important element of the EC’s proposed pharma strategy on antimicrobial resistance (AMR).